Novel Levofloxacin Derivatives as Potent Antibacterial Agents - Moshafi M. H.; N. Bahador; S. Moghimi; R. Ejtemaei; A. Foroumadi; Asadipour A. (Journal of Sciences, Islamic Republic of Iran)
In this report, a new series of fluoroquinolone agents which was derived from levofloxacin was synthesized and evaluated against Gram-positive (Bacillus subtillis, Staphylococcus aureus, Staphylococcus epidermidis and Micrococcus luteus) and Gram-negative (Esherichio coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Serratia marcescens) organisms. The results showed that some of the synthesized compounds are strong antibacterial agents. All the synthesized compounds showed remarkable activities against Staphylococcus epidermidis and Staphylococcus aureus (MIC = 0.03-1 µg/mL and 0.06-1 µg/mL respectively).